PERSEPSI KEAMANAN TRANSAKSI DALAM MEMPENGARUHI KEPUTUSAN BELANJA ONLINE MASYARAKAT KABUPATEN SUMBAWA MELALUI APLIKASI SHOPEE - Fitriyani, Ika; Mappuji, Rizky Ananda (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to determine the perception of transaction security in influencing online shopping decisions of Sumbawa District people through the Shopee application. The type of this study was associative study which aims to examine the effect of the perception of transaction security (X) on online shopping decisions of Sumbawa District people through the shopee application (Y). The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 96 people from Sumbawa District who had shopped online through the Shopee application. Determination of respondents in this study used a probability sampling technique with the purposive sampling method. The data used in this study was processed using the SPSS application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of this study indicate that the perception of transaction security had a positive and significant effect on online shopping decisions of Sumbawa District people through the Shopee application. The ability of the perception of transaction security variable to effect on online shopping decisions of Sumbawa District people through the Shopee application was 38.1%, while the remaining of 61.9% was effected by other factors not examined in this study, such as fast service, friend invitations, cashback voucher offers, ease of finding goods, low prices, and seller domicile.